2017
DOI: 10.1016/j.jvir.2016.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Image-Guided Cryoablation for the Treatment of Phantom Limb Pain in Amputees: A Pilot Study

Abstract: Purpose To prospectively evaluate percutaneous image-guided nerve cryoablation for treatment of refractory phantom limb pain (PLP) in a pilot cohort for purposes of deriving parameters to design a larger, randomized, parallel-armed, controlled trial. Materials and Methods From January 2015 to January 2016, 21 patients with refractory PLP underwent image-guided percutaneous cryoneurolysis procedures. Visual analog scale scores were documented at baseline and 7, 45, and 180 days after the procedure. Responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 41 publications
1
26
0
1
Order By: Relevance
“…Cryoablation involves the application of cold to nerves, creating a conduction block that can be retained chronically by inducing Wallerian degeneration of the nerve . This percutaneous, image‐guided surgery can be performed using minimally invasive techniques, and produced a 66% reduction in phantom pain up to 300 days in one study . Concomitant nerve coaptation and collagen nerve wrapping have been described to be effective as well in preventing painful neuromas and PLP after transfemoral amputation .…”
Section: Existing Treatments For Phantom Limb Painmentioning
confidence: 99%
“…Cryoablation involves the application of cold to nerves, creating a conduction block that can be retained chronically by inducing Wallerian degeneration of the nerve . This percutaneous, image‐guided surgery can be performed using minimally invasive techniques, and produced a 66% reduction in phantom pain up to 300 days in one study . Concomitant nerve coaptation and collagen nerve wrapping have been described to be effective as well in preventing painful neuromas and PLP after transfemoral amputation .…”
Section: Existing Treatments For Phantom Limb Painmentioning
confidence: 99%
“…These trials found promising effects of neuromodulation to alleviate PLP (low risk approach with high potential benefits). Other pilot studies concerned the application of sympathetic blocks (24) and cryoablation (12) for the treatment of PLP. In order to translate these techniques to clinical practice, the next step would be to conduct a pivotal trial.…”
Section: Clinical Trial Phases: Medical Device Studiesmentioning
confidence: 99%
“…We chose PLP given our experience designing trials for it as well as other neuropathic pain syndromes. Furthermore, PLP clinical trials have tested a variety of interventions including drugs (7,8), non-invasive brain stimulation (NIBS) (911), and invasive procedures (12). In addition, PLP is a disorder whose pathophysiology and optimum management remain elusive despite numerous studies.…”
Section: Introductionmentioning
confidence: 99%
“…As examples, the use of CT guidance for percutaneous cryoneurolysis in amputees has been reported for the management of phantom limb pain. 25 Fritz and coworkers have described MRI-guided cryoneurolysis of the sural nerve and posterior femoral cutaneous nerves to manage pain. 26,27 Kim and Ferrante reported using image guidance to cryoablate the obturator nerve for treatment of adductor spasticity.…”
Section: Introductionmentioning
confidence: 99%